2016
DOI: 10.1016/j.jpsychires.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 polyunsaturated fatty acid supplementation and white matter changes in major depression

Abstract: White matter abnormalities are implicated in major depressive disorder (MDD). As omega-3 polyunsaturated fatty acids (PUFAs) are low in MDD and affect myelination, we hypothesized that PUFA supplementation may alleviate depression through improving white matter integrity. Acutely depressed MDD patients (n=16) and healthy volunteers (HV, n=12) had 25-direction diffusion tensor imaging before and after 6 weeks of fish oil supplementation. Plasma phospholipid omega-3 PUFAs eicosapentaenoic acid (EPA) and docosahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 93 publications
2
36
1
Order By: Relevance
“…While our results indicate that DEF rats do not entirely recapitulate this general pattern, other factors associated with the human condition, including stress, inflammation, and genotype, may contribute and interact with n-3 PUFA status. It is notable, however, that, in healthy older adults [24] and patients with unipolar depression [25] fish oil supplementation is associated with increases in FA in multiple WM tracts, suggesting these variables are interrelated in human subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our results indicate that DEF rats do not entirely recapitulate this general pattern, other factors associated with the human condition, including stress, inflammation, and genotype, may contribute and interact with n-3 PUFA status. It is notable, however, that, in healthy older adults [24] and patients with unipolar depression [25] fish oil supplementation is associated with increases in FA in multiple WM tracts, suggesting these variables are interrelated in human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 (n-3) PUFAs including docosahexaenoic acid (DHA) and the omega-6 PUFA arachidonic acid (AA) have opposing effects on immuneinflammatory signaling, and metabolites of DHA have inflammation-resolving properties [16][17][18][19][20][21]. Importantly, emerging evidence suggests that PUFAs are associated with WMI in healthy subjects [22][23][24] and in patients with psychiatric disorders [25,26]. Meta-analyses indicate that schizophrenia [27], bipolar disorder [28], and unipolar depression [29] are associated with PUFA deficits including DHA.…”
mentioning
confidence: 99%
“…Frontal lobe connectivity with limbic structures is mediated in part by the uncinate fasciculus and superior longitudinal fasciculus, prominent white matter tracts that develop during gestation and undergo significant maturation during childhood and adolescence. Accumulating evidence suggests that n -3 PUFAs promote cortical white matter microstructural integrity [215], and a recent study found that fish oil supplementation increased white matter microstructural integrity and decreased depressive symptom severity in MDD patients [216]. Moreover, perinatal n -3 PUFA deficiency in monkeys [217], or low erythrocyte DHA biostatus in typically developing children [218], are both associated with reduced functional connectivity within prefrontal cortical networks.…”
Section: Neuropathophysiological Mechanismsmentioning
confidence: 99%
“…In animal experiments, thiamine-deprived rats had lower FA values 16 , while calorie restriction in rhesus macaques had increased FA 17 . Studies in human are also rare with limited evidence suggesting that vitamin B12 supplementation 18 , higher serum level of 25-hydroxyvitamin D 19 , plasma PUFA concentration 20 , and supplementation of Ω-3 PUFA 4 or fish oil 21 might be associated with favorable DTI metrics like higher FA values. However, except for one study showing adherence to the Mediterranean diet 22 was associated with higher FA values, whether and which nutritional or dietary factors directly from foods are related to white matter integrity is largely unknown.…”
Section: Introductionmentioning
confidence: 99%